2017
DOI: 10.1080/1547691x.2017.1397826
|View full text |Cite
|
Sign up to set email alerts
|

Divergent hypersensitivity responses following topical application of the quaternary ammonium compound, didecyldimethylammonium bromide

Abstract: Didecyldimethylammonium bromide (DDAB) is a fourth generation dialkyl-quaternary ammonium compound (QAC) that is used in numerous products for its antimicrobial properties. While many QACs have been associated with allergic disease, the toxicity and sensitization of DDAB have not been thoroughly investigated. The purpose of these studies was to evaluate the irritancy and sensitization potential of DDAB following dermal application in a murine model. DDAB induced significant irritancy (0.0625-2%), evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…To further evaluate type of hypersensitivity response induced by DDAC, IgE was evaluated following dermal exposure. Since we previously identified that exposure duration may influence the development of allergic responses (Shane et al ., 2017), IgE levels in mice exposed to DDAC for 14-days were assessed at 28 days post initial exposure. Mice (n=5) were treated for 14-days with DDAC and rested for 14-days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further evaluate type of hypersensitivity response induced by DDAC, IgE was evaluated following dermal exposure. Since we previously identified that exposure duration may influence the development of allergic responses (Shane et al ., 2017), IgE levels in mice exposed to DDAC for 14-days were assessed at 28 days post initial exposure. Mice (n=5) were treated for 14-days with DDAC and rested for 14-days.…”
Section: Methodsmentioning
confidence: 99%
“…To quantify serum IgE levels a standard colorimetric sandwich ELISA was performed according to manufacturer directions (Mouse IgE Ready-Set-Go!, eBioscience). To determine local production of IgE the IgE + B220 + (IgE + B-cells) population were analyzed by flow cytometry as previously described using IgE-FITC (R35–72) (BD Biosciences) (Shane et al ., 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, properties of chemical allergens and commensal bacteria add to the complex landscape of skin immunity. Many chemical sensitizers are also anti-microbial agents (Anderson et al 2010Shane et al 2017). While these agents may be beneficial in protecting against pathogenic bacteria, the influence of exposure on resident bacterial populations warrants further investigations.…”
Section: Skin Microbiomementioning
confidence: 99%
“…Quaternary ammonium compounds (QACs) are ubiquitous biocides (15), antiseptics (16), and widely used surface disinfectants (16). Exposure to QACs is associated with development of topical hypersensitivity (17) and asthma (18) especially in hospital settings (19). Although the exact mechanisms of how QACs modulate immune cell responses are unclear, QAC-induced allergic responses have been attributed to abrogated type 2 innate lymphoid cell responses (20).…”
Section: Introductionmentioning
confidence: 99%